2017
DOI: 10.1177/1521025117696822
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Validity of College Success Indicators for the At-Risk Student: Toward Developing a Best-Practice Model

Abstract: This study assessed the feasibility of using precollege success indicators to identify at-risk students at a large 4-year public research university in the Midwest. Retention data from students who participated in an established student success program were examined. The findings affirm that the initial admissions assessment identifying at-risk students is a feasible predictor of academic success, including high school (HS) grade point average (GPA) could predict student success over and above the variance acc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
4
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 30 publications
2
4
0
1
Order By: Relevance
“…Additionally, cumulative GPA at the beginning of the senior year was a strong predictor of student performance on the PSE and CCE. These results are similar to those reported by Tucker et al., who showed that GPA is a strong predictor of academic success ( p < 0.0001) 18,19 . Combining self‐confidence and GPA in clinical procedures could improve predictions of academic and clinical performance.…”
Section: Discussionsupporting
confidence: 90%
“…Additionally, cumulative GPA at the beginning of the senior year was a strong predictor of student performance on the PSE and CCE. These results are similar to those reported by Tucker et al., who showed that GPA is a strong predictor of academic success ( p < 0.0001) 18,19 . Combining self‐confidence and GPA in clinical procedures could improve predictions of academic and clinical performance.…”
Section: Discussionsupporting
confidence: 90%
“…Seidman (2005) asserts that improvements to college retention rates require early identification of students at risk of dropping out, coupled with early interventions aimed at aiding at-risk students, suggesting utilizing a "thorough examination of academic records' available to colleges upon student entry, including grades, courses taken, and standardized test scores" (p. 21). Tucker and McKnight (2017) found success identifying students at risk for non-retention at a public university in the Midwest by examining high-school grades and ACT scores upon entry, findings bolstered further when examining GPA after one semester in college. Other models for identifying at-risk students rely on surveys that measure student academic, social, and psychological attachment to college life, including Baker and Siryk's Student Adaptation to College Questionnaire (Baker & Siryk, 1986) and the recent Inventory of New College Student Adjustment developed by Watson and Lenz (2018).…”
Section: Surds Versus Early Alert Systemsmentioning
confidence: 88%
“…Similarly, Astin (2005) showed that university selectivity is a factor that positively correlates to student chances of completing a baccalaureate degree. A study conducted by Tucker and McKnight (2017) assessed precollege success indicators to identify at-risk students at a large 4-year public research university in the Midwest, and the retention data from the study confirmed that test scores, high school GPA, and first semester college GPA are good predictors of student success. Moreover, students who have a positive college experience are more likely to be satisfied with the college or university than students who do not have a positive college experience (DeShields et al., 2005).…”
Section: Prediction Of Satisfaction and Retention In Higher Educationmentioning
confidence: 92%
“…Professionals within the institutional research and planning office at the university where the study was conducted have reported that a set of specific factors have historically been the best predictors of student retention and satisfaction. These factors included academic achievement (GPA) and behavioral engagement in academic and nonacademic activities (Astin, 2005; DeAngelo, 2014; Freeman et al., 2007; Kuh et al., 2006; Tucker & McKnight, 2017). Therefore, we measured several of these variables to capture the common types of factors that often do well in predicting student retention and satisfaction.…”
Section: Methodsmentioning
confidence: 99%